2022
DOI: 10.1155/2022/5522828
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Secreted TGF-β1 Restores Treg/Th17 Skewing Induced by Lipopolysaccharide and Hypoxia Challenge via miR-155 Suppression

Abstract: Background. Regulatory T cell (Treg)/T helper (Th) 17 skewing is important in the development of acute respiratory distress syndrome (ARDS). Immunomodulatory effects of mesenchymal stem cell- (MSC-) secreted transforming growth factor- (TGF-) β1 on CD4+ T cells are environment-sensitive and lack discussion in hypoxic and inflammatory conditions. Methods. Mouse splenic CD4+ T cells were precoated with anti-CD3 (5 μg/ml) and anti-CD28 (2 μg/ml) overnight. RAW264.7 cells were added as antigen-presenting cells (AP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The pathophysiological mechanisms underlying ALI/ARDS involve the hyperaggregation and activation of platelets and leukocytes, enhanced permeability of the alveolar-capillary endothelial and epithelial barriers, infiltration by inflammatory cells, and the accumulation of protein-rich edematous fluid in the extravascular space (Liu et al 2022a , b ; He et al 2021 ). Th17 cells, a subset of CD4 + T cells, secrete IL-17 and play a pivotal role in mediating lung inflammation, contributing to the development of ARDS (Cheng et al 2022 ; Xue et al 2022 ). In this study, lung specimens from ARDS models underwent comprehensive pathomorphological analysis, focusing on edema, glycogen deposition, fibrosis, and inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms underlying ALI/ARDS involve the hyperaggregation and activation of platelets and leukocytes, enhanced permeability of the alveolar-capillary endothelial and epithelial barriers, infiltration by inflammatory cells, and the accumulation of protein-rich edematous fluid in the extravascular space (Liu et al 2022a , b ; He et al 2021 ). Th17 cells, a subset of CD4 + T cells, secrete IL-17 and play a pivotal role in mediating lung inflammation, contributing to the development of ARDS (Cheng et al 2022 ; Xue et al 2022 ). In this study, lung specimens from ARDS models underwent comprehensive pathomorphological analysis, focusing on edema, glycogen deposition, fibrosis, and inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, TGF-β1 is an essential regulator of cell proliferation, survival, and apoptosis; and TGF-β1 has anti-apoptotic effects in myelo-monocytic leukaemic cells co-cultured with stromal cells [ 52 ]. In addition, in an LPS-induced ARDS mouse model, MSCs overexpressing TGF-β1 could regulate lung inflammation and attenuate lung injuries by modulating the imbalance of Th17/Treg in the lungs [ 53 ]. We also found TGF-β1 participate the immunosuppression and anti-apoptosis pathways of IL18-hUCMSC in vitro and in vivo, by using the Fresolimumab (GC1008) and TGF beta-1,2,3 monoclonal antibody to block the activity of TGF-β1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that mesenchymal stem/stromal cell-secreted TGFB could regulate Treg production to relieve inflammation. Interestingly, TGFBI also belongs to the TGFB family, which may affect T-cell function through another pathway [ 46 , 47 ]. The complete mechanism by which TGFBI regulates the immunosuppressive capacity of hUC-MSCs still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%